(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Levels of lead, cadmium, and nickel in roadside soils and vegetables along a major highway in Gazipur, Bangladesh were investigated. Soil samples were collected at distances of 0, 50, 100, and 1000 m (meter) from the road. The concentrations of lead (Pb) and nickel (Ni) in soil and vegetables (bottle gourd and pumpkin) decreased with distance from the road, indicating their relation to traffic and automotive emissions. The concentration of cadmium (Cd) was found to be independent of distance from road. There were significant differences in the concentrations of lead, cadmium, and nickel for different plant species and soils at various distances. The heavy metals contents both in the soils and vegetables for every distance from the road was found in the order nickel>lead>cadmium. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11170 Bangladesh J. Agril. Res. 37(1): 9-17, March 2012